Efficacy and safety of the ICD in patients with catecholaminergic polymorphic ventricular tachycardia. (3rd October 2022) - Mazzanti, A; Trancuccio, A; Kukavica, D; Marino, M; Giannini, G; Rossetti, L; Memmi, M; Bloise, R; Morini, M; Napolitano, C; Priori, S G
Abstract: Background: Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) is a potentially fatal genetic arrhythmia syndrome and, despite optimal beta-blocker (BB) therapy, patients often experience life-threatening arrhythmic events (LAE). The role of implantable cardioverter defibrillators (ICD) on reducing mortality in patients with CPVT is debated. Purpose: 1) To assess the survival benefit of ICD in the overall CPVT population; 2) to investigate the benefit-to-harm ratio in the population of CPVT patients carriers of ICD. Methods: We followed-up consecutive patients with genetically-proven CPVT, treated with optimal BB mono-therapy. The probability of surviving at the occurrence of a first LAE (defined as: sudden cardiac death, aborted cardiac arrest or hemodynamically non-tolerated ventricular tachycardia) during BB mono-therapy was compared between ICD carriers and non-ICD carriers. In the cohort of ICD carriers, we assessed the rate of a first major complication (i.e., a complication requiring surgical intervention) and we calculated the benefit-to-harm ratio of ICD (defined as rate of appropriate shocks on LAE over rate of major complications). Results: We enrolled 228 CPVT patients with a pathogenic RYR2 (n=216) or CASQ2 (n=12) mutation, of whom 87 (38%) had an ICD implanted. Overall, during 1, 558 person-years of follow-up, 31/228 (14%) patients experienced a first LAE on BB mono-therapy (annual LAE rate 2.0%, 95% CI: 1.4–2.8%). Of the 31 individuals who experienced an LAE, 21 patients had an ICD when the LAE occurred, and all survived after ICD intervention. Of the remaining 10 patients who were not carriers of an ICD, 6/10 (60%) survived after external defibrillation or spontaneous arrhythmia termination, while 4/10 (40%) died suddenly. The probability of surviving at the occurrence of a first LAE in BB mono-therapy was thirty-fold higher (Odds Ratio: 30.0, 95% CI: 1.4–629.0; p=0.029) in patients with an ICD, as compared to patients without an ICD. Overall, 15/87 (17%) patients with an ICD experienced a first major complication over 602 person-years of follow-up (2.5% per year, 95% CI: 1.4%-4.1%). Importantly, no patient died for a pro-arrhythmic effect or complications related to ICD. Comparing the rate of major complications to the rate of appropriate ICD shocks on LAE (LAE rate 4.7% per year, 95% CI: 3.1–7.0%), the benefit-to-harm ratio was 1.9, thus favouring the benefit of ICD therapy. Conclusions: In our population, ICD therapy conferred a significant survival benefit in patients with CPVT at the occurrence of a first LAE. Overall, the benefit of ICD implant outweighed the harm, as shown by almost two times greater benefit-to-harm ratio. This study provides evidence supporting ICD implantation in patients with high-risk CPVT. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ricerca Corrente Funding Scheme of the Italian Ministry of Health